Auctions with Signaling Bidders: Optimal Design and Information Disclosure - Olivier Bos; Martin Pollrich (CESifo GmbH, 2025)
We study optimal auctions in a symmetric private values setting, where bidders have signaling concerns: they care about winning the object and a receivers inference about their type. Signaling concerns arise in various economic situations such as takeover bidding, charity auctions, procurement and art auctions. We show that auction revenue can be decomposed into the standard revenue from the respective auction without signaling concern, and a signaling component. The latter is the bidders' ex-ante expected signaling value net of an endogenous outside option: the signaling value for the lowest type. The revenue decomposition restores revenue equivalence between different auction designs, provided that the same information about bids is revealed. Revealing information about submitted bids affects revenue via the endogenous outside option. In general, revenue is not monotone in information revelation: revealing more information about submitted bids may reduce revenue. We show that any bid disclosure rule allowing to distinguish whether a bidder submitted a bid or abstained from participation minimizes the outside option, and therefore maximizes revenue.
Keywords: D44; D82; 330; optimal auctions; revenue equivalence; Bayesian persuasion; information design